The Methodology of Quality Matrix in Manufacturing Quality Process Improvement - Dian, Milan (Manufacturing Technology Journal, 2013)
In each industrial entrepreneur organization around the globe a three dimensional objective well known under the abbreviation QCD (Quality, Costs, and Delivery) is examined, pursued, and evaluated on daily basis. The nowadays crucial philosophy pertaining to process improvement in terms of quality assurance and significant cost reduction is that: ``The quality must be manufactured and not controlled up''. In order to be successful on the market place it is necessary to orchestrate, implement and carry out an advanced production quality assurance system with appropriate tools of course accompanying with previously precisely organized prototype and pre-serial stages of production. The article deals with a proposal of adequate methodology and the experimental implementation of quality matrix into manufacturing process assurance in order to improve a quality level and the whole QCD.
Keywords: process improvement; quality assurance; quality tools; quality matrix